Challenges in managing adherence in patients with cardiovascular disease (review) - Yu. S. Ignatova; Ya. I. Bryukhanov; T. B. Pecherina; O. L. Barbarash (Сибирский научный медицинский журнал)
Cardiovascular diseases (CVD) remain one of the main problems in most countries of the modern world. In this connection, maintaining adherence to the treatment and prevention of CVD is a priority in the fight against diseases of the cardiovascular system. According to the WHO, insufficient adherence to treatment is an urgent medical problem. Approximately 35 % of patients cancel taking medications within a year after an acute cardiovascular event, which leads to a threefold increase in the risk of complications. The purpose of the review is to highlight the problem of low adherence in the aspect of CVD and highlight the main methods of increasing adherence to treatment. This article reflects the main aspects of adherence management, considers the factors leading to a decrease in the level of disease control, identifies the causes of low adherence, and identifies methods for increasing adherence to treatment in patients with CVD.